Ecology of populations - Ranta, Esa (Ecology, biodiversity, and conservation., 2006)
"The theme of the book is the distribution and abundance of organisms in space and time. The core of the book lies in how local births and deaths are tied to emigration and immigration processes, and how environmental variability at different scales affects population dynamics with stochastic processes and spatial structure, and it shows how elementary analytical tools can be used to understand population fluctuations, synchrony, processes underlying range distributions, and community structure and species coexistence."--Jacket.